Educational and cultural challenges: digital technologies in higher education - Ramos, Natália (2024)
In the last decade we’ve been observing several changes in education, namely the introduction of a more open and digital education, aligned with the transformation of society, today more global and technological. Another significative change that has been observed in the past decades is the transformation into a multicultural society strongly characterized by increased migration, what brought a lot of challenges regarding intercultural communication, integration and interpersonal and intercultural relations.The inclusion of technology helps minimize these impacts facilitating intercultural communication, and also allowing greater cross-cutting accessibility to the education of the various students around the world regardless of their country of residence, as long as they can access to a computer and internet connection. The objective of this article is to analyze the impacts of the use of digital technologies. By including technology, in the pedagogical model, we are taking advantage of the information society and solidifying the relations between knowledge and society, improving social integration and intercultural relations, as well as developing a more open, inclusive, digital and networked education. Higher Education must be open and inclusive at all levels and for all students who attend it.